Controls on Cyclic Formation of Quaternary Early Diagenetic Dolomite. Issue 8 (16th April 2018) - McCormack, J.; Bontognali, T. R. R.; Immenhauser, A.; Kwiecien, O.
Abstract: The origin of sedimentary dolomite and the factors that control its formation within the geological record remain speculative. In most models, dolomite formation is linked to evaporative conditions, high water temperature, increasing Mg/Ca ratio, increasing alkalinity, and high amounts of biomass. Here we challenge these archetypal views, by documenting a case example of Quaternary dolomite which formed in Lake Van at constantly low temperature (<4°C) and without direct control of the latter conditions. Dolomite occurs within highstand sediments related to suborbital climate variability (Dansgaard‐Oeschger cycles). We propose that dolomite precipitation is a product of a microbially influenced process, triggered by ecological stress, resulting from reventilation of the water‐sediment interface. Independently from the validity of this hypothesis, our results call for a reevaluation of the paleoenvironmental conditions often invoked for early diagenetic dolomite‐rich intervals within sedimentary sequences and for caution when interpreting time series of subrecent lacustrine carbonates. Plain Language Summary: The mineral dolomite is a common constituent of many ancient rock formations, including important hydrocarbon reservoirs and sedimentary sequences that are studied for paleoclimatic reconstructions. Because dolomite is very difficult to precipitate in laboratory experiments that simulate Earth's surface conditions, the key factors controlling its occurrence in the geological record remain speculative and debated. Through the study of subrecent sediments recovered from a deep alkaline lake, we show that warm and evaporitic conditions, as well as other factors commonly considered crucial for dolomite formation, are not as essential as traditionally thought. Consequently, the interpretation of several dolomite‐rich sedimentary sequences may require a substantial re‐evaluation. Key Points: Dolomite formation is not directly controlled by water temperature, Mg/Ca ratio, salinity, pH, alkalinity, or amount of biomass Cyclic occurrence of dolomite in sediments of deep alkaline Lake Van is controlled by orbital and suborbital climate variability Paleoenvironmental reconstructions based on factors commonly considered crucial for dolomite formation may require reevaluation